2012
DOI: 10.3748/wjg.v18.i6.576
|View full text |Cite
|
Sign up to set email alerts
|

Study onRIZ1gene promoter methylation status in human esophageal squamous cell carcinoma

Abstract: Promoter methylation may play an important role in the epigenetic silencing of RIZ1 gene expression in human ESCC. RIZ1 is considered to be a potential tumor suppressor gene and may be a biological parameter for testing early stage human ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Lal et al (27) demonstrated that RIZ1 expression is lost in thyroid tumor cell lines and is also significantly reduced in thyroid carcinomas, when compared with normal thyroid tissues (p<0.0001) and benign tumors (p=0.0003). Wen dong et al (28) found that RIZ1 gene is silenced in human esophageal squamous cell carcinoma and it is concentration is down regulated. Finaly Khaenam et al (29) found that (RIZ1) inactivated by promoter hypermethylation in patients with liver fluke-related cholangiocarcinoma (CCA).…”
Section: Discussion:-mentioning
confidence: 99%
See 2 more Smart Citations
“…Lal et al (27) demonstrated that RIZ1 expression is lost in thyroid tumor cell lines and is also significantly reduced in thyroid carcinomas, when compared with normal thyroid tissues (p<0.0001) and benign tumors (p=0.0003). Wen dong et al (28) found that RIZ1 gene is silenced in human esophageal squamous cell carcinoma and it is concentration is down regulated. Finaly Khaenam et al (29) found that (RIZ1) inactivated by promoter hypermethylation in patients with liver fluke-related cholangiocarcinoma (CCA).…”
Section: Discussion:-mentioning
confidence: 99%
“…It is the 2 nd most common malignancy related mortality worldwide with 745,000 deaths per year (2). Its incidence is continuously increasing throughout the world (3)(4)(5). In Egypt, between 1993 and 2002, there was an almost two fold increase in HCC among patients with chronic liver disease (6).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that RIZ1 was decreased (t = -57.738, p = 0.000) while RIZ2 was uniformly present in ESCC carcinoma (t = -1.180, p = 0.249) compared with the corresponding normal tissue specimens. Promoter region high methylation status serves as an important mechanism in RIZ1 down regulation or deletion [8,22]. In this study RIZ1 promoter region aberrant methylation was detected by MSP in ESCC cell line EC109.…”
Section: Discussionmentioning
confidence: 99%
“…RIZ1 was proved to be a tumor suppressor gene in ESCC in our previous studies, whereby RIZ1 was lowly expressed or deleted in ESCC tumor tissues and cell lines. Promoter region aberrant methylation serves as an important role [8,22]. In this paper Real-time PCR was used to examine both the expression levels of RIZ1 and RIZ1 + RIZ2 mRNA in ESCC carcinoma and corresponding normal tissue specimens.…”
Section: Discussionmentioning
confidence: 99%